PENGARUH MODEL PEMBELAJARAN INTERAKTIF TERHADAP MOTIVASI BELAJAR SISWA - Raztiani, Hissan; Permana, Indra (IKIP Siliwangi, 2019)
Successful learning is carefully arranged to learn. Learning with media can be a way for teachers so students can enjoy learning. Successful learning is fun learning that can make the student feel comfortable and have no pressure. Therefore it is very important for teachers to create student learning that is comfortable and active without pressure. The purpose of conducting this research is to provide an overview of how the responses given by students during the learning process are interactive. This type of research is the implementation of research development using interactive learning methods and the results by distributing questionnaires and observations. The results of the research in this article show that students are more active in working in learning and able to communicate well. Then students also provide responses and opinions about the application of interactive learning which according to students is more interesting. Therefore the research in this article can be said that the media of interactive learning are feasible to be used in the process of learning Indonesia both in the classroom and in learning independently to improve understanding and quality and provision of students learning.